Neutrophil lymphocyte ratio and severity of acute kidney injury in septic children - Kowita, Nurul Huda; Sovira, Nora; Safri, Mulya; Ismy, Jufitriani; Haris, Syafruddin; Herdata, Heru Noviat; Bakhtiar, Bakhtiar (Indonesian Pediatric Society, 2023)
Background Acute kidney injury (AKI) in sepsis is associated with an inflammatory process in kidney microcirculation and may increase morbidity and mortality in children. The neutrophil lymphocyte ratio (NLR) is an inflammatory biomarker of the inflammatory process in sepsis. Objective To determine the role of NLR in predicting the severity of AKI and to describe the demographic and laboratory characteristics, as they relate to outcomes of pediatric patients with AKI and sepsis. Methods This cross-sectional study was conducted in the PICU at Dr. Zainoel Abidin General Hospital (RSUDZA), Banda Aceh, Aceh. Medical record data were obtained from critically ill children with sepsis and AKI. Chi-square test was used to compare the proportions of each variable. We also calculated odds ratios to evaluate the AKI severity, PELOD-2 score, and patient outcomes. Spearman's analysis was used to look for a possible correlation between NLR and AKI severity in septic children. Results Seventy-one subjects with sepsis and AKI were included. Subject characteristics were as follows: 63.4% males, 63.4% < 1 year of age, 56.3% with respiratory problems as a primary disease, 38% with AKI injury stage, and 54.9% subjects with PELOD-2 score ?10. There was no significant correlation between AKI severity and mortality (OR 3.04; 95%CI 0.990 to 9.378; P=0.052). Subjects with a PELOD-2 score ?10 had a 47.6 times higher chance of mortality in septic children with AKI compared to those with PELOD-2 scores <10. There was no correlation between NLR and AKI severity (r=0.019; P=0.878). Conclusion There is no correlation between NLR and AKI severity. Sepsis accompanied by AKI may increase the risk of mortality in children. Septic children with more severe AKI tends to be less survive.